THE CORRELATION BETWEEN SEX AND AGE WITH THE HISTOPATHOLOGY OF LUNG CANCER PATIENTS IN Dr. SARDJITO HOSPITAL 2010 - Pakaya, David; Maramis, Maynard Andrew; Setyawati, Tri (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2017)
Introduction: Lung cancer is the world's highest incidence and mortality. Sex and age are risk factors that affect the incidence of lung cancer besides smoking behavior. These risk factors associated with histopathologic which to base a diagnosis of lung cancer.Objective: To analyze the correlation of sex and age with histopathological of lung cancer patients who were treated at the Dr. Sardjito Hospital in 2010.Methods: The study was a retrospective cross-sectional design. Conducted at the Medical Records of Dr. Sardjito Hospital in February 2016. The samples were all lung cancer patients (total sampling) who were treated at the Dr. Sardjito Hospital from January 2010 - December 2010. The data was processed with SPSS software ver. 21.0 and analyzed with Chi square. Results: The male is that most lung cancer patients are 41 (62.1%). The age group most lung cancer patients in the age group > 40 years were 58 cases (87.9%). NSCLC is the most common histopathology of 60 people (90.9%). After analyzed with Chi square test the data showed p=0.810 for sex with histopathological correlation and p=0,095 for the age with histopathological correlation. Conclusions: There was no correlation between sex and age with histopathology of lung cancer patients who were treated at the Dr. Sardjito Hospital in 2010.Â Keywords: Sex, age, histopathology, lung cancer